The meanest man in Texas [videorecording (DVD)] - Ward, Justin (Director); Ward, Mateus; McShane, Jamie; Bard, Alexandra (Ammo Content, 2019)
After shooting two men in self-defense, Clyde is convicted of murder and sentenced to death. Just hours before execution, the governor spares him and ships him to the Texas Prison Farm to serve hard labor, where he gains the moniker 'The Meanest Man in Texas.' Clyde's journey consists of some life-changing highs and lows, but ultimately leads him to redemption.